Biphenyl hydrogenation over supported transition metal catalysts under supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, C. V.; Sato, O.; Shirai, M. (Applied Catalysis A - General, 2005)
Catalytic hydrogenation of biphenyl to bicyclohexyl, an organic hydrogen storage medium, was examined over supported transition metal catalysts in supercritical carbon dioxide solvent. The yield of bicyclohexyl was almost 100% over the charcoal-supported rhodium (Rh/C) and ruthenium (Ru/C) catalysts at the temperature of 323 K, which was much lower than that required for biphenyl hydrogenation in organic solvents (573 K). The initial activity was higher over the Rh/C catalyst, while the initial selectivity to bicyclohexyl was higher over the Ru/C catalyst. The conversion of biphenyl increased with increase in hydrogen and carbon dioxide pressures, while the selectivity to bicyclohexyl was independent of hydrogen and carbon dioxide pressures over both catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: bicyclohexyl; biphenyl; charcoal-supported rhodium catalyst; charcoal-supported ruthenium catalyst; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide